PENGARUH PENERAPAN E-LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI DI KELAS XI SMK PUTRA KUALUH TELUK PULAI DALAM KUALUH LEIDONG - Aisyah, Aisyah (Fakultas Agama Islam, 2021)
The progress of science and technology is increasingly rapidly in the current global era, its influence is felt in people's lives. The need for a concept and mechanism for teaching and learning information technology-based education is inevitable. The concept, which was later known as E-Learning, had the effect of transforming conventional education into digital form, both in terms of content and system. This study aims to determine the learning outcomes of Islamic Religious Education in the application of E-Learning, as well as the effect of the application of E-Learning on learning outcomes of Islamic Religious Education at SMK Putra Kualauh Teluk Pulai Dalam. The population in this study were all students of SMK Putra Kualuh, the research sample was set at 35 students. The collection tool used is a questionnaire on the results of the application of E-Learning in the form of a multiple-choice objective of 20 questions that are tested after participating in learning using E-Learning. The results obtained from this study are the average value of Islamic Religious Education learning outcomes (questionnaire) of students after being taught using E-Learning is 9.4 very good category. From the results of the hypothesis test, it is known that the use of E-Learning in the learning process can increase motivation and effectiveness in learning. The application of E-Learning can foster student enthusiasm in participating in learning activities carried out and be able to encourage students to achieve higher learning outcomes.